Mechanism and stability of an Fe-based 2D MOF during the photoelectro-Fenton treatment of organic micropollutants under UVA and visible light irradiation. (1st October 2020) - Ye, Zhihong; Schukraft, Giulia E.M.; L'Hermitte, Anouk; Xiong, Ying; Brillas, Enric; Petit, Camille; Sirés, Ignasi
Abstract: This work reports the novel application of an Fe-based 2D metal−organic framework (MOF), prepared with 2, 2′-bipyridine-5, 5′-dicarboxylate (bpydc) as organic linker, as highly active catalyst for heterogeneous photoelectro-Fenton (PEF) treatment of the lipid regulator bezafibrate in a model matrix and urban wastewater. Well-dispersed 2D structures were successfully synthesized and their morphological, physicochemical and photocatalytic properties were assessed. UV/Vis PEF using an IrO2 /air-diffusion cell with an extremely low catalyst concentration (0.05 g L −1, tenfold lower than reported 3D MOFs) outperformed electro-oxidation with electrogenerated H2 O2, electro-Fenton and visible-light PEF. Its excellent performance was explained by: (i) the enhanced mass transport of H2 O2 (and organic molecules) at the 2D structure, providing active sites for heterogeneous Fenton's reaction and in-situ Fe(II) regeneration; (ii) the ability of photoinduced electrons to reduce H2 O2 to OH, and Fe(III) to Fe(II); and (iii) the enhanced charge transfer and excitation of Fe–O clusters, which increased the number of electron-hole pairs. LC-QToF-MS and GC-MS allowed the identification of 16 aromatic products of bezafibrate. The complete removal of four micropollutants mixed in urban wastewater at pH 7.4 revealed the great potential of (Fe−bpydc)-catalyzed PEF process. Graphical abstract: Image 1 Highlights: Fe−based 2D MOF degrades various organic micropollutants at mild pH via PEF catalysis. Complete degradation of bezafibrate by UV/Vis PEF using only 0.05 g L −1 Fe−based 2D MOF. 16 primary oxidation products of bezafibrate detected by LC-QToF-MS and GC-MS. Detailed mechanism for PEF with Fe−based 2D MOF: heterogeneous Fenton + photocatalysis. Thorough study on the stability, recyclability and electronic structure of Fe−based 2D MOF.